Evidence of Impact from a National Digital Entrepreneurship Apprentice Program in Malaysia - Mohd Zaidi Abd Rozan (CV. Literasi Indonesia, 2022)
Impact Digital Entrepreneurship Apprentice Program (IDEA@KPT) at Ministry of Higher Education Malaysia 2021 is a comprehensive nationwide six-month program. Forty-three teams consist of 43 Academic Supervisors, 129 institutes of Higher Learning students, and 43 Micro & Small Enterprises (MSE) owners conducted by Universiti Teknologi Malaysia. The program is aimed to develop capable students in maneuvering the digital business world. Students underwent an online Business and Digital Training, with apprenticeship and formal reportings. This article aims to present the impact of IDEA@KPT activities by analyzing 43 case studies produced in the program. A pre-codification scheme that concentrates on the study goals was the method for data collection. Before the program, all the teams were informed of the required components to ensure uniformity of the report. The evidence of significant gain and impact on the MSEs businesses was drawn from the components. Other than the components, analytics hindsight, visual appeal, persuasion ability, perception on paid ads, posting timing, and synergies beyond the digital world activities were gathered, providing richer information and insights that increase business value. Such lessons are beneficial to all parties as all businesses are demanded to utilize digital platforms nowadays.